(untitled) (Studia austriaca, 2018)
Edition and commentary of a rediscovered polemic from the year 1918, titled «Ein offiziöser Gschaftlhuber der Kultur [An Officious Busybody of Culture]», published by Hermann Broch under the pseudonym K. L. Hib in Die Wage. Eine Wiener Wochenschrift, Vol. 21, Issue 27 of July 6, 1918, pp. 433-8. The text is a biting critique of the anthropogeographer Erwin Hanslik (1880-1940), co-founder and director of the Institut für Kulturwissenschaft in Vienna.